Microhabitat association and population status of the Luwuk introduced Banggai cardinalfish (Pterapogon kauderni Koumans, 1933) population - Novalina Serdiati; Abdul Gani; Deddy Wahyudi; Abigail Mary Moore; Samliok Ndobe (Depik, 2021)
The Banggai cardinalfish Pterapogon kauderni is the Indonesian national marine ornamental fish mascot, and an object of national and international conservation concern. The endemic population of this species is limited to the Banggai Archipelago in Central Sulawesi, Indonesia and a few nearby islands in North Maluku. In addition, introduced populations have become established, mainly along ornamental fish trade routes. The National Action Plan for Banggai Cardinalfish Conservation (NAP-BCFC) calls for monitoring and management of all P. kauderni populations. A survey of the Luwuk introduced P. kauderni population was carried out in October 2021.   Data were collected at three sites with established P. kauderni populations: the ferry harbour, public harbour (Teluk Lalong) and a recreational area on the nearby coast (Kilo 5). P. kauderni were recorded by microhabitat association and size class (recruits, juveniles, adults). Data collected were compared with data from previous surveys where available. With the exception of one group in a sea anemone at Kilo 5, all P. kauderni were associated with Diadema sea urchins (D. setosum at all sites; D. savignyi at Kilo 5). At Kilo 5 P. kauderni the population structure indicates the possible capture of market-sized juveniles. Overall abundance was also lower compared to the polluted but unfished harbours. The proportion of recruits was significantly negatively correlated with the ratio of adult P. kauderni to Diadema urchins. The results will inform regional legislation currently in preparation to support sustainable management of P. kauderni populations, habitat and microhabitat in Central Sulawesi, as well as contributing to NAP-BCFC targets.Keywords:Banggai cardinalfishEndangered speciesDiademaMicrohabitat,MonitoringOrnamental fisheryLocal regulation